Digest - Herfarth, Christian; Lehnert, Thomas (The British journal of surgery, 1998)
For a previous quarter's digest, Professor Christian Herfarth and Dr Thomas Lehnert selected the best from the July to September 1997 issues of Der Chirurg. A digest for the BJS for the same period, which was written by Mr Colin Johnson, appeared in the German journal.
Gesehen am 01.10.2025